2018
DOI: 10.15414/jmbfs.2018.8.2.756-759
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity and Mineral Content of Rocket (Eruca Sativa) Plant From Italian and Bulgarian Origins

Abstract: Rocket plant (Eruca sativa) is a green leafy vegetable with significant levels of bioactive active components. Although, this plant is known in Bulgaria, scanty data concerning chemical composition of representatives with Bulgarian origin is available. The aim of this study was to evaluate and to compare the biological potential of Italian and Bulgarian rockets in terms of their antioxidant activity, total phenolic content and total hydroxycinnamic acid derivatives. The micro- and macro elements were evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 14 publications
0
10
0
1
Order By: Relevance
“…[ 12 ] Matev et al. [ 13 ] revealed that E. sativa leaves have potential as a source of natural antioxidants; Corleto et al. [ 14 ] mentioned that E. sativa may be considered as a functional food, since it is a good source of flavonoids (with quercetin, kaempferol, and isorhamnetin being predominant).…”
Section: Introductionmentioning
confidence: 99%
“…[ 12 ] Matev et al. [ 13 ] revealed that E. sativa leaves have potential as a source of natural antioxidants; Corleto et al. [ 14 ] mentioned that E. sativa may be considered as a functional food, since it is a good source of flavonoids (with quercetin, kaempferol, and isorhamnetin being predominant).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, 2.84 ± 0.005 mg/100 g of zinc was found in Ficus capensis from Nigeria [ 93 ]. The range of zinc in Romanian plants was between 20.83 ± 1.11 μ g/kg in Lavandula angustifolia and 64.76 ± 0.53 μ g/kg in Althaea officinalis [ 94 ], while the leaves of Eruca sativa from Italia and Bulgaria revealed a zinc content of 15.07 ± 0.60 mg/kg and 91.05 ± 0.65 mg/kg, respectively [ 95 ] ( Table 2 ).…”
Section: Phytomedicines and Covid-19mentioning
confidence: 99%
“…A report on the quantitative estimation of quercetin by reverse-phase HPLC in the methanol extract of gerger leaves from Saudi Arabia was also available [41]. Bulgarian and Italian gerger studied for the total phenolic content, and the antioxidant potential of ethanol extract suggested a higher antioxidant capacity in Bulgarian gerger than the Italian variety [24]. The method of extraction of food antioxidants affects the nature of compounds isolated, and the quality of the total antioxidant activity [42].…”
Section: Journal Of Food and Nutrition Researchmentioning
confidence: 99%
“…Flavanol glycosides of gerger leaf improved the well-being of the cardiovascular system [19], possess anticancer activity [20], and the fatty acids of gerger leaves were able to induce adipogenic activity, thereby implicated in diabetes [21]. The methanol extract of gerger leaves was able to exhibit in-vivo antioxidant activity in rats [22], and the ethanolic extract improved the reproduction in male rats [23], also show in-vitro free radical scavenging activity [24]. The essential oil extracted from gerger leaves contain erucin, an isothiocyanate derivative shown to exhibit anticancer, antibacterial, and free radical scavenging activities [25,26].…”
mentioning
confidence: 99%